GE_GERICHTE P/15930/2020 vom 19. März 2025 - GE Cour de justice (2025)
LÉSION CORPORELLE SIMPLE;RIXE;EXPULSION(DROIT PÉNAL);TORT MORAL | CP.122; CP.133; CPP.333.al1; CP.123; CP.66a; LAA.24; CPP.122; CO.41; CP.67b